Value of Nucleolar Organizer Regions count in cervical pathology (Journal of Pathology of Nepal, 2012)
Background: ‘AgNOR’ represents Nucleolar Organiser Regions stained with silver which are related to cell proliferation rate and tumor malignant potential. The objective of this study was to evaluate the role of AgNOR in differentiating benign and precancerous lesions from cancerous lesions in both cervical smears and histology. Materials and Methods: This was a prospective study conducted at Manipal Teaching Hospital, from July 2005 to June 2007. Women of suspected cervical pathology and who underwent pap smears test followed by subsequent biopsy were included. There were 53 cases were included out of which 11 cases were of high grade squamous intraepithelial lesion and 12 cases of low grade squamous intraepithelial lesion, and 10 cases each of carcinoma, chronic cervicitis with and without squamous metaplasia. Results: In Low grade squamous intraepithelial lesion meanAgNOR dots was < (2.9 in pap smears and 1.9 in histology) in high grade lesion (3.45 in pap smears and 3.00 in histology). In carcinoma meanAgNOR dots was 5.18 and 4.05 in pap smears and histology respectively. Subjective AgNOR Pattern Assessment in pap smears and in histology was increasing with significant difference from intraepithelial lesions to carcinoma. Conclusion: In cervical pathology, the number and shape of AgNOR dots change from benign to precancerous to malignant tumors. Similarly, AgNOR Pattern Assessment is useful in differentiating benign to intraepithelial lesions to carcinoma cases. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6017 JPN 2012; 2(3): 180-185